The promise and challenges of deep learning models for automated histopathologic classification and mutation prediction in lung cancer - Patil, Pradnya D.; Hobbs, Brian; Pennell, Nathan A. (Journal of Thoracic Disease; Vol 11, No 2 (February 26, 2019): Journal of Thoracic Disease, 2018)
The histologic subclassification of tumors as either squamous cell carcinoma or adenocarcinoma is used by convention to guide systemic chemotherapy for patients diagnosed with non-small cell lung cancer (NSCLC) (1,2). The current gold standard for histopathologic classification of tissue specimens is visual microscopic inspection of tissue specimens by pathologists.